The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acscatal.2c03298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrolyte Media on the Catalysis of Fe Phthalocyanine toward the Oxygen Reduction Reaction: Ab Initio Molecular Dynamics Simulations and Experimental Analyses

Abstract: FeN4 macrocycles are among the most promising nonprecious metal catalysts for the oxygen reduction reaction (ORR). Nevertheless, these catalysts perform poorly in acidic media. To understand what impedes the use of these catalysts in acid, graphite electrodes were drop-coated with inks of iron phthalocyanine adsorbed on carbon nanotubes (FePc-CNTs), and the electrocatalytic behavior of the catalyst was studied in four different supporting electrolytes (i.e., HCl, H2SO4, CH3COOH, and NaOH) by means of cyclic vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 119 publications
1
10
0
Order By: Relevance
“…Linear sweep voltammetry (LSV) is an electrochemical technique in which the applied potential between the working electrode (WE) and the reference electrode (RE) is controlled as a function of time at a given velocity (d E /d t , v , V s –1 ) within a range of potentials. This is an excellent technique for the characterization of modified electrode surfaces (see brief experimental method description in ref ) based on the electrochemical determination of the amounts of metal active centers using the Faraday laws and for the calculation of the thermodynamic and kinetic parameters associated with these processes. When the direction of the scan is reversed, this technique is called cyclic voltammetry or CV.…”
Section: Thermodynamic Parameter From Electrochemical Experimentsmentioning
confidence: 99%
“…Linear sweep voltammetry (LSV) is an electrochemical technique in which the applied potential between the working electrode (WE) and the reference electrode (RE) is controlled as a function of time at a given velocity (d E /d t , v , V s –1 ) within a range of potentials. This is an excellent technique for the characterization of modified electrode surfaces (see brief experimental method description in ref ) based on the electrochemical determination of the amounts of metal active centers using the Faraday laws and for the calculation of the thermodynamic and kinetic parameters associated with these processes. When the direction of the scan is reversed, this technique is called cyclic voltammetry or CV.…”
Section: Thermodynamic Parameter From Electrochemical Experimentsmentioning
confidence: 99%
“…[7][8][9][10][11][12] Since cobalt phthalocyanine (CoPc) with a CoN 4 structural unit was first reported as the cathode catalyst for FCs in 1964, 13 transition metal phthalocyanine (TMPc) has been extensively investigated. 7,11,[13][14][15][16][17][18][19][20][21][22][23] Transition metal polyphthalocyanine complexes (TMPPcs), which are composed of multiple TMPcs linked in various ways, have received widespread attention as electrochemical catalysts due to their high electrochemical activity, large surface area, good electrical conductivity and excellent electrocatalytic stability. Xu et al reported that planar CoPPc supported on carbon (CoPPc/C) with an active unit of CoN 4 was synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…For PGM-free catalysts to replace Pt in practical PEMFC devices, it is necessary to match and ideally surpass both the activity and the durability of the current Pt-based catalysts. While much progress has been achieved in obtaining PGM-free ORR catalysts with activity matching that of Pt catalysts, the durability of PGM-free ORR catalysts is still far from meeting the requirements for practical use. Furthermore, due to the possibility of multiple catalyst degradation pathways and the difficulty of studying degradation processes at the microscopic level, descriptors for PGM-free catalyst durability are currently unavailable. This is in contrast to the well-known computational hydrogen electrode approach pioneered by Nørskov and co-workers that has identified the adsorption energies of OH (and also O and OOH) intermediates as the key descriptor of activity corresponding to the experimentally observed onset potential ( V onset ). Thus, it is necessary to identify simple energetic descriptors that can guide the design of more durable catalysts. Additionally, for a more precise design of highly active catalysts, descriptors beyond simple E ads,OH are necessary.…”
mentioning
confidence: 99%